Pengembangan Ekonomi Pariwisata Lokal Berbasis Maqashid Syaria: Participatory Appraisal of Competitive Advantage: - Siti Fatimatul Khasanah (Syntax Idea)
This research aims to analyze the development of local tourism economy using the Participatory Appraisal of Competitive Advantage (PACA) approach through the perspective of Maqashid Shariah. The study takes a case in Pulau Merah, Sumberagung Village, Pesanggaran District, Banyuwangi Regency. This research adopts a qualitative approach with descriptive analysis. Data collection is conducted through observation, interviews, and documentation. The research subjects are selected using a purposive technique. The study finds two PACA indicators that fulfill four out of the six elements of Maqashid Shariah in the local tourism economy of Pulau Merah. This research recommends strengthening institutional synergy among the government, private sector, and community to create added value in the tourism sector management, ensuring that all aspects of Sapta Pesona are fulfilled and have a positive impact on the local community in line with Maqashid Shariah principles.